Sufficient conditions for Hamiltonian graphs in terms of (signless Laplacian) spectral radius. Issue 5 (4th May 2018) - Chen, Xiaodan; Hou, Yaoping; Qian, Jianguo
Abstract : Let G be a simple graph with n vertices, m edges and minimum degree . In this paper, we prove that if then G is Hamiltonian with only a few exceptions. Using this result, we present some spectral sufficient conditions for a graph to be Hamiltonian in terms of the spectral radius or signless Laplacian spectral radius of the graph. Our results improve some previous work.